Does Islamic Corporate Governance Moderation The Influence of Sharia Financial Performance Toward Islamic Social Reporting? - Wairooy, Fatimah Az-zahra; Haryono, Slamet (Universitas Muhammadiyah Surakarta, 2023)
This study examine to retest the influence of Sharia Financial Performance towards Islamic Social Reporting with Islamic Corporate Governance as a moderation variable (empirical study on Indonesia Islamic Commercial Bank from 2016-2021). The hypothesis examine by using MRA regression and panel data regression. The population in this research are all the Islamic Commercial Banks that listed on OJK from 2016-2021. The sampling methods that used in this research is purposive sampling and could manage to obtained 66 sample from 11 Islamic Commercial Banks. The results shows that Return On Assets, Ruturn On Equity, and Financing to Debt Ratio influenced the disclosure did Islamic Social Reporting, whereas Capital Adequacy Ratio, Debt to Equity Ratio, and Investment Account Holder did not influenced the Islamic Social Reporting. Furthermore frequency of board of commissioner could influenced Financing to Debt Ratio, and Investment Account Holder towards deepening of Islamic Social Reporting, frequency of audit committee meeting could be moderating Investment Account Holder towards strengthening Islamic Social Reporting, While the frequency of sharia supervisory board meeting could moderating Financing to Debt Ratio towards Islamic Social Reporting. The findings of this study can be important input for regulators to properly regulate the number of meetings of each board in influencing Islamic Financial Performance as a tool in disclosing their Islamic Social Reporting.